Macrophage-enriched novel functional long noncoding RNAs LRRC75A-AS1 and GAPLINC regulate polarization and innate immune responses - Valverde, Araceli; Naqvi, Raza Ali; Naqvi, Afsar R. (Inflammation research, 2024)
Introduction Macrophages (Mφs) are functionally dynamic immune cells that bridge innate and adaptive immune responses; however, the underlying epigenetic mechanisms that control Mφ plasticity and innate immune functions are not well elucidated. Objective To identify novel functions of macrophage-enriched lncRNAs in regulating polarization and innate immune responses. Methods Total RNA isolated from differentiating monocyte-derived M1 and M2 Mφs was profiled for lncRNAs expression using RNAseq. Impact of LRRC75A-AS1, GAPLINC and AL139099.5 knockdown was examined on macrophage differentiation, polarization markers, phagocytosis, and antigen processing by flow cytometry and florescence microscopy. Cytokine profiles were examined by multiplex bead array and cytoskeletal signaling pathway genes were quantified by PCR-based array. Gingival biopsies were collected from periodontally healthy and diseased subjects to examine lncRNAs, M1/M2 marker expression. Results Transcriptome profiling of M1 and M2 Mφs identified thousands of differentially expressed known and novel lncRNAs. We characterized three Mφ-enriched lncRNAs LRRC75A-AS1, GAPLINC and AL139099.5 in polarization and innate immunity. Knockdown of LRRC75A-AS1 and GAPLINC downregulated the Mφ differentiation markers and skewed Mφ polarization by decreasing M1 markers without a significant impact on M2 markers. LRRC75A-AS1 and GAPLINC knockdown also attenuated bacterial phagocytosis, antigen processing and inflammatory cytokine secretion in Mφs, supporting their functional role in potentiating innate immune functions. Mechanistically, LRRC75A-AS1 and GAPLINC knockdown impaired Mφ migration by downregulating the expression of multiple cytoskeletal signaling pathways suggesting their critical role in regulating Mφ migration. Finally, we showed that LRRC75A-AS1 and GAPLINC were upregulated in periodontitis and their expression correlates with higher M1 markers suggesting their role in macrophage polarization in vivo. Conclusion Our results show that polarized Mφs acquire a unique lncRNA repertoire and identified many previously unknown lncRNA sequences. LRRC75A-AS1 and GAPLINC, which are induced in periodontitis, regulate Mφ polarization and innate immune functions supporting their critical role in inflammation.